(3eLGdS aj GdehGYX GdefGSHGJ dBjGJ ShQI GdYfcHhJ aj GdCMGOjK hGdeSGFd hGdMcGjGJs - (3eLghds ((3YKeGf Hf hdjs)
(3ChdgG (B:s
(3fGbU GdNWHI, hChdg(B: (3aj GdehGYX GdefGSHGJ dBjGJ ShQI GdYfcHhJ aj GdCMGOjK hGdeSGFd hGdMcGjGJ hGdehGYX aj Cf GdCfTG Hd GdeDefhf dG jJQchf aj GdOfjG Ydi GdUMI hGdSdGeIs
(3BNQgG (B:s
(3MJi JNQL Nda XghQge Ke jYWhG cJHge HTeGFdge ef hQGA XghQge cPG aj GdHOhQ GdSGaQI TQM gPG GdMOjK aj GdeQbGI hajV GdbOjQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs